Hello, Baby Shark - Bajet, John John (2020)
"Say hello to Baby Shark and all his friends!"--Back cover
On board pages.
Cover title.
"A Baby Shark book!"--Cover
Keywords: Sharks -- Juvenile fiction; Friendship -- Juvenile fiction; Requins -- Romans, nouvelles, etc. pour la jeunesse; Amitié -- Romans, nouvelles, etc. pour la jeunesse; Friendship; Sharks; Board books; picture books; novels; Novels; Picture books; Board books; Fiction; Juvenile works; Board books; Picture books; Fiction; Novels; Livres d'images.; Romans